Moral intelligence 2.0 : enhancing business performance and leadership success in turbulent times - Lennick, Doug (Essential lessons on leadership., 2011)
The best-performing companies have leaders who actively apply moral values to achieve enduring personal and organizational success. Lennick and Kiel extensively identify the moral components at the heart of the recent financial crisis, and illuminate the monetary and human costs of failed moral leadership in global finance, business and government. The authors begin by systematically defining the principles of moral intelligence and the behavioral competencies associated with them. Next, they demonstrate why sustainable optimal performance-on both an individual and organizational level-requires the development and application of superior moral and emotional competencies. Using many new examples and real case studies and new interviews with key business leaders, they identify connections between moral intelligence and higher levels of trust, engagement, retention, and innovation. Readers will find specific guidance on moral leadership in both large organizations and entrepreneurial ventures, as well as a new, practical, step-by-step plan for measuring and strengthening every component of moral intelligence-from integrity and responsibility to compassion and forgiveness. The authors also provide practical ways for readers to develop their own moral and emotional competencies.